Satisfacción laboral y su relación con algunas variables ocupacionales en tres municipalidades - Alfaro Salazar, Ronald (2012)
Because of the important role of district municipalities or local governments in the development and the country’s economy, it is important to ensure the achievement of their goals. Therefore, there should be available, qualified, motivated and satisfied personnel; so that, a study of job satisfaction in three district municipalities of Lima and Callao is presented. The research involves measurement of job satisfaction and analysis of its relation to occupational variables: (a) Labor Condition (b) Gender and (c) Service time in each one of the three municipalities, as well as the comparison of the overall satisfaction level. The research is descriptive and correlational with a quantitative approach, the same as was performed on a sample of 82, 126 and 161 workers in each of the three municipalities under study. To measure job satisfaction a questionnaire was used “Escala de Opiniones SL-SPC" (Palma, 2005), which has four factors: (a) Significance of Task (b) Working Conditions (c) Personal Recognition / or Social, and (d) Economic Benefits. The main results are that there are not significant differences in the job satisfaction level of the workers in each of the three municipalities, and it can be regarded as average; moreover, that if there are significant differences for labor condition in regards to the satisfaction level with their various factors in each.